2021
DOI: 10.1029/2021jg006546
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Typhoon “Mangkhut” on Surface Water Nutrient and Chlorophyll Inventories of the South China Sea in September 2018

Abstract: The influence of the exceptionally strong typhoon Mangkhut on the availability of nutrients and changes in primary production were studied in the northern South China Sea in September 2018. A tight station grid was sampled to analyze major nutrients, chlorophyll_a, particulate and dissolved organic carbon and nitrogen. Based on interpolated profiles, nutrients and organic matter budgets were determined for the upper 100 m of the water column prior to and after Mangkhut's passage. An upper layer of 100 m was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the offshore region away from the river plume, the Chla change was attributed to advection and vertical mixing, which was consistent with the findings of previous studies (Liu et al., 2013; S. Pan et al., 2017; Zhao et al., 2009). In response to typhoons, both nutrients and sediments have been suggested to change (Kuss et al., 2021; Li et al., 2021), which may lead to delayed Chla changes. This study showed that the biological process in response to typhoon‐perturbed nutrients was generally stronger in the nearshore region than in the offshore region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the offshore region away from the river plume, the Chla change was attributed to advection and vertical mixing, which was consistent with the findings of previous studies (Liu et al., 2013; S. Pan et al., 2017; Zhao et al., 2009). In response to typhoons, both nutrients and sediments have been suggested to change (Kuss et al., 2021; Li et al., 2021), which may lead to delayed Chla changes. This study showed that the biological process in response to typhoon‐perturbed nutrients was generally stronger in the nearshore region than in the offshore region.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al, 2017;Zhao et al, 2009). In response to typhoons, both nutrients and sediments have been suggested to change (Kuss et al, 2021;Li et al, 2021), which may lead to delayed Chla changes. This study showed that the biological process in response to typhoon-perturbed nutrients was generally stronger in the nearshore region than in the offshore region.…”
Section: Model Diagnosis Of Chla Changementioning
confidence: 99%
“…In the SCS, the nutricline and the chlorophyll maximum layer are always below the mixed layer (Kuss et al, 2021). When the mixed layer after a TC is deeper than the chlorophyll maximum layer, a high Chl-a concentration can be transmitted to the sea surface (Wang et al, 2010); when the mixed layer is deeper than the nutricline, more nutrients are transported to the euphoric layer, which promotes the growth of phytoplankton (Palter, 2015).…”
Section: Seasonal Variation Of Tc-induced Chl_enmentioning
confidence: 99%